2006
DOI: 10.1590/s1677-04202006000400001
|View full text |Cite
|
Sign up to set email alerts
|

Utility of basic research in plant/crop physiology in relation to crop improvement: a review and a personal account

Abstract: Utilidade da pesquisa básica em fisiologia vegetal e em fisiologia da produção em relação ao melhoramento das culturas: uma revisão e uma análise pessoal: A pesquisa e o desenvolvimento agrícola têm função essencial no desenvolvimento econômico das nações, provendo segurança alimentar para uma população em constante crescimento demográfico. Em países desenvolvidos, as lacunas entre a produção potencial e a produção real são sobremodo estreitas, devido a uma combinação de tecnologias avançadas, novas variedades… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 146 publications
(212 reference statements)
0
13
0
Order By: Relevance
“…The role of physiological research in crop improvement and cropping systems management has recently been reviewed (El-Sharkawy, 2006b). As a branch of basic science, plant physiological research has a fundamental role in advancing the frontier of knowledge that is essential for the better understanding of plants and their interactions with surrounding biophysical environments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of physiological research in crop improvement and cropping systems management has recently been reviewed (El-Sharkawy, 2006b). As a branch of basic science, plant physiological research has a fundamental role in advancing the frontier of knowledge that is essential for the better understanding of plants and their interactions with surrounding biophysical environments.…”
Section: Introductionmentioning
confidence: 99%
“…Those authors concluded that field research is the only valid ecosystem research in studying plant water relations and crop photosynthesis in relation to productivity. Until recently, the controlled-environment and greenhouse potted-plant scientists (many of whom were members of national science academies) controlled the plant photosynthesis and water relations research and often invoked the misuse of the terminology "adaptation to stress" for "acclimation to stress" to protect their domination over the public-funded scientific establishment and to cover up their failure in contributing to the early discoveries of the C 4 photosynthesis and its implications for plant water use efficiency (El-Sharkawy, 2005, 2006bHesketh, 1965, 1986;Begonia and Begonia, 2007). This is not a very good example to teach young people about how science is done nor an efficient way to manage public-funded research.…”
Section: Introductionmentioning
confidence: 99%
“…Seasonal variation of P. lactifl ora decrease ratio Rfd correlates with the potential CO 2 fi xation rate of leaves. When Rfd ≥ 2.5 the normal photosynthetic activity is indicated and on the other hand, at Rfd < 1 the low photosynthetic activity was confi rmed (El-Sharkawy, 2006). The chlorophyll fl uorescence indices were measured during the vegetation period of P. lactifl ora.…”
Section: Methodsmentioning
confidence: 99%
“…Zelitch 1971Zelitch , 1982 on what the agronomists did some being done at his location at Connecticut Agricultural Experiment Station, carefully citing most of the proper sources; the early agronomic work was also cited enough to win two citation classics. The American mainstream plant physiological-biochemical photosynthetic scientists also missed the Berkeley, CA, ground-breaking work on photosynthetic C 3 biochemistry (for the history of the elucidation of the C 3 cycle see Calvin 1989), as well as work on internode-dwarfing and flowering genes and their role in the photosynthesis of crop canopies and subsequent yield that impacted positively agricultural productivity and food security worldwide in the past five decades (the so-called "Green Revolution", mainly funded by non-profit private agencies) (Borlaug 1983, El-Sharkawy 2005, 2006a, Begonia and Begonia 2007, Andre 2006. American mainstream plant physiologicalbiochemical photosynthetic scientists seem to have drifted somewhat during all this.…”
Section: Tropical Grasses (C 4 Species)mentioning
confidence: 99%
“…Thus, in these complex and expensive FACE trials that require large interdisciplinary/interinstitution team of researchers, it would be of importance to extensilvely study effects of edapho-climatic conditions, particularly soil-waternutrient factors and air humidity within crop canopy, and to construct complementary crop-soil-atmosphere submodels. Such information is essential in order to elucidate mechanisms underlying responses to elevated CO 2 in the field, to maximise benefit/cost ratio of doing research as well as to reasonably predict the effect of global climate change on agricultural productivity (Rosenzweig and Parry 1994, El-Sharkawy 2005, 2006a, IPCC 2006. In any case, however, these data indirectly illustrate the invalidity of the high estimates of CO 2 around Rubisco in bundle sheath cells of C 4 plants via the so-called 'CO 2 -concentrating mechanism' that were based on unrealistic theoretical models.…”
Section: Discovery Of Leaf Kranz Anatomy and Its Implications For Phomentioning
confidence: 99%